2008
DOI: 10.1007/s10439-008-9450-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network-Based Evaluation of Chronic Non-Thermal Effects of Modulated 2450 MHz Microwave Radiation on Electroencephalogram

Abstract: The effects of chronic exposure (2 h daily for 21 days) of 1 kHz square wave-modulated 2450 MHz microwave radiation (non-thermal) on sleep-EEG, open field behavior, and thyroid hormones (T(3), T(4), and TSH) have been analyzed in an animal model. Results revealed significant changes in these pathophysiological parameters (p < 0.05 or better), except body temperature, grooming behavior, and TSH levels. The sleep-EEG power spectrum data for slow wave sleep (SWS), rapid eye movement (REM) sleep, and awake (AWA) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This experimental result confirmed the strong influence of the nonthermal effects of MWs on the activity of animal cells. Sinha et al 67 studied the influence of the nonthermal effects of MWs on electroencephalogram (EEG) of rats that were chronically exposed to MW irradiation. Sleep- EEG, open field behaviour, and thyroid hormones (T3, T4, and Thyroid stimulating hormone (TSH)) were analysed, and the authors observed significant changes in all examined pathophysiological parameters except body temperature, grooming behaviour, and TSH levels.…”
Section: Applications Of and Harms That Are Caused By The Nonthermal ...mentioning
confidence: 99%
“…This experimental result confirmed the strong influence of the nonthermal effects of MWs on the activity of animal cells. Sinha et al 67 studied the influence of the nonthermal effects of MWs on electroencephalogram (EEG) of rats that were chronically exposed to MW irradiation. Sleep- EEG, open field behaviour, and thyroid hormones (T3, T4, and Thyroid stimulating hormone (TSH)) were analysed, and the authors observed significant changes in all examined pathophysiological parameters except body temperature, grooming behaviour, and TSH levels.…”
Section: Applications Of and Harms That Are Caused By The Nonthermal ...mentioning
confidence: 99%
“…Another aspect where new insights into electrical and electromagnetically cell-tocell coupling in the brain could have an impact is the research about the effect of external electromagnetic fields (caused by technical devices such as cell phones) on neurophysiological processes. Non-thermal effects not yet understood (e.g., Bawin et al, 1973;Huber et al, 2002;Sinha et al, 2008;Schmid et al, 2012;Mohammed et al, 2013) could possibly be explained by considering the electrical and endogenous electromagnetic processes in brains. Finally, the inclusion of the novel cell-to-cell communication modes in models about cognitive processes, and ultimately about consciousness, could lead to new insights.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 99%
“…However, they neglect the possible health hazards caused by the non-thermal effects. To data, numerous studies have shown or indicated that the nonthermal effects of microwave could cause various types of molecular transformations and alterations by disturbing the weak bonds which could cause special microscopic biological effects (protein synthesis [3]- [7], genotoxicity [8]- [13] oxidative stress [14]- [18], cell signaling [19]- [22], brain EEG [23], cell apoptosis [24] [25], sperm motility [26] and etc.). From the macro perspective, non-thermal effects of microwave might cause heat shock [3], infertility [7] [18], auditory system buzzing sound [27] , visual loss [28] and etc.…”
Section: Introductionmentioning
confidence: 99%